Divinylsulfonamides enable the construction of homogeneous antibody–drug conjugates. Issue 23 (1st December 2020) - Huang, Rong; Sheng, Yao; Wei, Ding; Lu, Wenwen; Xu, Zili; Chen, Hongli; Jiang, Biao
Graphical abstract: Abstract: Methods that site-specifically attach payloads to an antibody with controlled DAR (Drug-Antibody Ratio) are highly desirable for the generation of homogeneous antibody-drug conjugates (ADCs). We describe the use of N -phenyl-divinylsulfonamide scaffold as a linker platform to site-specifically construct homogeneous DAR four ADCs through a disulfide re-bridging approach. Several monomethyl auristatin E (MMAE)-linkers were synthesized and the drug-linkers that contain electron-donating groups on the phenyl of the linker showed high stability. Her2-targeted MMAE-linker-herceptin and EGFR targeted MMAE-linker-cetuximab conjugates were prepared. The conjugates demonstrated high efficacy and selectivity for killing target-positive cancer cells in vitro . The EGFR-targeted conjugates also showed significant antitumor activities in vivo .